Kemampuan Literasi Informasi Mahasiswa dan Peranan Perpustakaan Dalam Proses Belajar Mengajar di Perguruan Tinggi - Umar Falahul Alam (IAIN Ponorogo, 2013)
A skill of Information literacy for students is very important. This capability will be useful in any search activity information that students need. The development of information and communication technology can greatly support the achievement of good teaching and learning process when coupled with the information literacy skills. The information literacy capability of students and higher education are two inseparable things. Therefore students need information literacy skills to support their learning process at university. Besides that, University libraries have a big role to create the students or academic community to be the literate person. The right steps in organizing information obtained will create a responsibility and independence person. If any student has information literacy skills, no exaggeration to say that the teaching and learning process will go well, and it certainly will create a generation that is able to learn long life in his life.